Wellness Patchwork - A Wellness Phenomenon of Our Age - Printz-Markó, Erzsébet; Darabos, Ferenc; Ivancsóné Horváth, Zsuzsanna (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2017)
In our research we reviewed the spectrum of the health tourism, the models of the wellness tourism. Our questionnaire survey proceeds along Ardell’s model, which we conducted at multiple-generation Hungarian spas. With the help of it we discovered the wellness tourism habits of the Hungarian population. Our research had 547 participants. According to our supposition the wellness cannot be done effectively if our leisure time and everyday philosophy of life conflicts. Is the wellness wellness in the people’s minds as well or is it just a new fad that we ‘go wellness’, empty words, behind which the content vanishes? Our survey verified our earlier research results: currently, the wellness tourism for the majority of the tourists is still none other than relaxation spiced up with fun elements. A change of paradigm would be needed for us to be able to efficiently participate in health care programs, really serving our health, thus shaping our lives. This change of aspect applies both to the supply and the demand sides.